Ascorbic Acid Sensitizes Colorectal Carcinoma to the Cytotoxicity of Arsenic Trioxide via Promoting Reactive Oxygen Species-Dependent Apoptosis and Pyroptosis - Tian, Wei; Wang, Zhuo; Tang, Nan-nan; Li, Jia-tong; Liu, Yu; Chu, Wen-Feng; Yang, Bao-Feng (Frontiers in Pharmacology, 2020)
Arsenic trioxide (ATO) is an effective therapeutic agent against acute promyelocytic leukemia (APL); however, its anti-tumor effect on solid tumors such as colorectal cancer (CRC) is still in debate. Ascorbic acid (AA) also produces a selective cytotoxic activity against tumor cells. Here, we exploit the potential benefit of ATO/AA combination in generating cytotoxicity to CRC cells, which may lay the ground work for the potential combinational chemotherapy of CRCs. According to the results, we found that ATO and AA effectively inhibited the viability of human CRC cells in a synergistic manner. AA and ATO corporately activated caspase-3 to trigger apoptosis and upregulated the expression of caspase-1and promoted formation of inflammasomes to induce pyroptosis. Furthermore, the stimulation of ROS overproduction was demonstrated as a subcellular mechanism for apoptosis and pyroptosis induced by ATO/AA combination treatment. Our findings suggest that ATO combination with a conventional dosage of AA offers an advantage for killing CRC cells. The synergistic action of ATO/AA combination might be considered a plausible strategy for the treatment of CRC and perhaps other solid tumors as well.